Ring-shaped molecules as split ring resonators of a molecular metamaterial - Lindlein, Norbert; et al. (Photonic Metamaterials: From Random to Periodic, META 2006, 2006)
We analytically analyse the magnetic response of ring shaped molecules. We find that circular symmetry must be broken and that transitions between higher order states have to be enabled to ob-tain a reasonable magnetic response. © 2006 Optical Society of America.